2020
DOI: 10.1186/s12936-020-03405-3
|View full text |Cite
|
Sign up to set email alerts
|

Costing malaria interventions from pilots to elimination programmes

Abstract: Background Malaria programmes in countries with low transmission levels require evidence to optimize deployment of current and new tools to reach elimination with limited resources. Recent pilots of elimination strategies in Ethiopia, Senegal, and Zambia produced evidence of their epidemiological impacts and costs. There is a need to generalize these findings to different epidemiological and health systems contexts. Methods Drawing on experience of implementing partners, operational documents and costing stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The cost of MDA varied from ∼$1.04 to $19.40 USD per person per round; one study estimated that drugs accounted for 70% of the cost of MDA. 49 On the lower end, Gabaldon and Guerrero 50 estimated a cost of $0.11 to $0.21 USD per person per visit, depending on distance between houses, (approximately $1.04 to $1.99 in 2021 USD). Cirera et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost of MDA varied from ∼$1.04 to $19.40 USD per person per round; one study estimated that drugs accounted for 70% of the cost of MDA. 49 On the lower end, Gabaldon and Guerrero 50 estimated a cost of $0.11 to $0.21 USD per person per visit, depending on distance between houses, (approximately $1.04 to $1.99 in 2021 USD). Cirera et al.…”
Section: Resultsmentioning
confidence: 99%
“…Galactionova et al. 49 estimated an initial cost of $2.35 USD per person treated per round in the first year, dropping to $2.19 USD per person per round if implemented annually for 5 years, and that MDA would be more expensive than other interventions such as rapid reporting, reactive case detection, or indoor residual spraying. This same study also noted that aspects such as sensitization and training may overlap between programs such as MDA and reactive case detection and that co-implementation might provide overall improvements in cost-effectiveness.…”
Section: Resultsmentioning
confidence: 99%
“…HSS costs per child were $230, $143, and $354 in Uganda, Nigeria, and DR Congo, while rectal artesunate-specific costs were $92, $76, and $110, respectively. We present absolute variation in startup, annually recurring, and total costs per child at risk and per child treated in table 2 (gross total costs and per-child costs by programme component are shown in appendix 2 pp 20-21; sensitivity analysis is presented in appendix 2 pp [22][23]. Costs per child younger than 5 years are substantially higher in DR Congo than in Uganda or Nigeria due to the large financing requirements for monitoring and evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…Several other studies have encouraged the integration of health system constraints into costing as a crucial step towards realistic budgeting and cost-effectiveness analyses, across a range of diseases. [19][20][21][22][23] Due to CARAMAL's focus on severe disease and the health system constraints at different levels of the system, comparing our estimates with costs of other malaria interventions might be misleading. A review of the costs of CHW programmes in low-income and middle-income countries found only seven studies reporting these on malaria, with large heterogeneity in methods and scope.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we limited our assessment to the test interventions used in the trial, and used RACD and/or no RAVC as a comparison. It is possible that comparisons with other approaches, including non-targeted interventions, and/or use of a different control (eg, no RACD), would also be cost effective 41…”
Section: Discussionmentioning
confidence: 99%